Lehninger Principles of Biochemistry - Nelson, David L Cox, Michael M (W.H. Freeman, 2008)
Presenting the fundamentals of biochemistry through selected topics, the fifth edition of this text contains the latest developments in the field, such as new treatments in metabolic regulation, coverage of DNA-based information technologies and a new graphical style for enzyme reaction mechanisms.